Kejadian karies gigi dilihat dari kebersihan gigi mulut , konsumsi air minum, perilaku jajanan dan pendidikan ibu pada murid Madrasah Ibtidaiyah Al-Irsyad Desa Sungai Tandipah Kecamatan Sungai Tabuk Kabupaten Banjar - Salamah, Siti; Hidayati, Sri; Sari, Emilda (Journal of Oral Health Care, 2020)
According to the 2013 Riskesdas, Indonesian population with dental and oral health problems in the last 12 months is 36.1% and experienced a history of dental caries with an average amount of tooth decay of 7.2 teeth per person, 5 teeth have been removed or can no longer be maintained. On average, each person in Banjar District has almost 8 teeth with caries, which means higher than the national average of 5 teeth. The purpose of this study was to determine the incidence of dental caries in terms of oral hygiene, drinking water consumption, food behavior and mother's education. Case study research with quantitative research to determine and analyze the incidence of dental caries in students of Al-Irshad Madrasah Ibtidaiyah. The samples were 174 people with a total sampling technique. The results of the study were mostly caries in the high category, most of the oral hygiene was in the moderate category, water based river used as drinking water contained high iron (fe), low fluorine (f) and acidic pH, the snack consumption behaviour was mostly good, while maternal education was mostly basic education. Suggestions for health workers to increase UKGS activities through promotive, preventive and curative efforts and to train small doctors, water supply should be treated before consume, addition of fluorine to food and drinks, use of fluorine toothpaste, supervision of school canteens and health education.